6ER-011 Real world adherence to multiple sclerosis therapy. (24th March 2020) - Rodrigues, M; Soares, A; Almeida, P; Alcobia, A; Vargas Gomes, M; Andreozzi, V; Félix, J
Abstract : Background and importance: Good adherence to disease modifying therapy for multiple sclerosis is associated with a reduced risk of relapse, maximising the beneficial effects of treatment. Hospital pharmacists are key healthcare professional in patient therapy management and adherence. Aim and objectives: The study aimed to assess adherence to multiple sclerosis therapy in a real world setting. Material and methods: This was a retrospective cohort study based on drug hospital pharmacy claims for multiple sclerosis. Patients with at least one drug claim for multiple sclerosis (interferon, fingolimod, dimethyl fumarate, glatiramer acetate, natalizumab or teriflunomide) were identified from a general hospital, between 2012 and 2017. Adherence was evaluated using medication possession ratio (MPR), defined as the total number of days with drug supply divided by the observation period. Adherence was calculated at 6, 12 and 24 months. Only patients who had a drug claim between 30 days before the defined time point or anytime until the end of follow-up were included. Patients with an MPR ≥80% were considered adherent to therapy. Results: There were 269 patients with at least 6 months of follow-up: mean age at first drug claim was 42.2 (SD 10.7) years. Six month, 12 month and 24 month adherence rates (MPR ≥80%) were as follows: interferon (n=149) 94.0%, 87.2% and 67.1%; glatiramer (n=55) 78.2%, 70.9% and 56.4%; natalizumab (n=18) 94.4%, 83.3% and 66.7%; and fingolimod (n=15) 73.3%, 80.0% and 66.7%. Overall adherence with injectable drugs seemed higher at any time point than oral drugs: injectable drugs 93.6% (6 months), 86.7% (12 months) and 70.0% (24 months) compared with 73.5%, 70.6% and 55.9%, respectively, for oral drugs. Conclusion and relevance: This retrospective analysis showed high 6 month to 24 month adherence rates for injectable DMD in multiple sclerosis. Both interferon and natalizumab had higher adherence rates than reported elsewhere in the literature. Oral DMD had lower adherence rates than injectable DMD but more consistent rates with other studies in the literature. 1 References and/or acknowledgements: 1. Duquette P, Yeung M, Mouallif S, et al. A retrospective claims analysis: Compliance and discontinuation rates among Canadian patients with multiple sclerosis treated with disease modifying therapies. PLOS One 2019;14:e0210417. No conflict of interest.